Uma psicanalista que faz cinema - Chnaiderman, Miriam (Percurso, 2008)
Realização: Andréa Carvalho Mendes de Almeida, Bela M. Sister, Danielle Breyton, Renata Puliti, Silvio Hotimsky e Susan Markuszower